Investigation of Anticancer Activity of Lindernia crustacea (L.) F. Muell. var. Crustacean - BARUSRUX, Sahapat; WEERAPREEYAKUL, Natthida; PHIBOONCHAIYANAN, Preeyaporn Plaimee; KHAMPHIO, Munthipha; TANTHANUCH, Waraporn; THUMMANU, Kanjana (Walailak Journal of Science and Technology (WJST), 2018)
Lindernia crustacea (L.) F. Muell. var. crustacean or “Ya Kap Hoi: YKH” was misunderstood as “Ya Yad Nam Kang” and cancer curative. This study aimed to investigate anticancer activity by the analysis of chemical constituent in extracts and in vitro screening of biological activities of the extract in several aspects such as cancer cell lines cytotoxic activity, immune cell proliferating activity, reducing power activity, alkylation activity. The HPLC analysis showed the absence of plumbagin peak observed in the HPLC chromatograms of both YKH aqueous and YKH ethanolic extracts. The YKH ethanolic extract yielded more chemical constituents than that of the YKH aqueous extract. The YKH aqueous extract was inactive against all cancer cells tested. Interestingly, YKH ethanolic extract caused cancer cell death in HCT116 colon cancer, HepG2 liver cancer, and Jurkat leukemic cancer cell lines in the concentration dependent manner. The following IC50 concentrations of the YKH ethanolic extract that possessed 50 % cell death after 24 h exposure in HCT116, HepG2, and Jurkat cell line were 195.4 ± 12, 171.7 ± 8.7, and 48.8 ± 5.7 µg/mL, respectively. Both aqueous and ethanolic extracts of YKH showed high antioxidant activity based on reducing power activity but did not have alkylation activity. At high concentration (250 µg/mL), YKH ethanolic extract can inhibit immune cells proliferation activity more than the YKH aqueous extract. An unexpected but critical outcome of our studies was the finding that anticancer activity is promised by selecting the plant extraction solvent with less polarity. Potential anticancer constituents were extracted from YKH using ethanol and these constituents cannot be found in aqueous solution of YKH.